Richardson number criteria for direct-contact-condensation-induced thermal stratification using visualization - Jo, Byeongnam; Erkan, Nejdet; Okamoto, Koji (Progress in Nuclear Energy, 2020)
This study aims to suggest a dimensionless number to determine the formation and disappearance of thermal stratification induced by direct contact condensation in a 1/20 scaled-down suppression pool of the Fukushima Daiichi nuclear power plant. The modified Richardson number, which represents the ratio of buoyancy force to inertia of steam, was employed to explain the thermal stratification in the suppression pool. Steam condensation experiments were performed at both sub-atmospheric and atmospheric pressures. A blow-down pipe with an inner diameter of 12.7 mm was used to inject and condense steam in the suppression pool. The effects of steam mass on the thermal stratification behaviors were examined by varying the steam mass flow rate (mass flux) from 0.50 kg/hr (1.10 kg/m2·s) to 2.50 kg/hr (5.48 kg/m2·s). The steam condensation was visualized using a high-speed camera. In the results, thermal stratification was successfully reproduced in this study, and it was observed that the behaviors of thermal stratification (vertical temperature profile) was affected by the steam mass flow rate and the subcooling temperature. The Richardson number was evaluated by measuring the size and frequency of steam bubbles. The time evolution of the Richardson number was analyzed with vertical temperature profiles of water in the suppression pool. The critical Richardson number, which determines the formation and disappearance of thermal stratification, was suggested to be of the order of 1.
Keywords: Critical Richardson number; Dimensionless number; Direct contact condensation; Fukushima dai-ichi nuclear power plants; Richardson number; Subcooling temperature; Suppression pool; Vertical temperature profile; Direct contact condensation; Richardson number; Suppression pool; Thermal stratification; Visualization